Compression and denoising of speech transmission using Daubechies wavelet family. (2017) - Sheikh, Javaid A.; Parah, Shabir A.; Akhtar, Sakeena; Bhat, G. Mohiuddin
Over the past few years there has been much work done on compression and enhancement of speech signals. Efficient speech compression techniques are becoming hectic with the fast growth of data and multimedia services. In this paper, wavelet-based analysis, processing and compression of multimedia signals like speech are described and implemented. A wavelet-based speech compression and speech denoising techniques obtained by using hard and soft thresholding algorithm are presented. Daubechies wavelets have been implemented on a test recorded speech signal for compression and denoising purposes. It has been found that the proposed work shows better results as compared to the already existing technique. Moreover, soft thresholding is preferable over hard thresholding with higher PSNR and less MSE. The results obtained have been found satisfactory as compared to existing state-of-the-art techniques.